2014
DOI: 10.1002/jhm.2153
|View full text |Cite
|
Sign up to set email alerts
|

Specialties performing paracentesis procedures at university hospitals: Implications for training and certification

Abstract: BACKGROUND Paracentesis procedure competency is not required for internal medicine or family medicine board certification, and national data show these procedures are increasingly referred to interventional radiology (IR). However, practice patterns at university hospitals are less clear. OBJECTIVE To evaluate which specialties perform paracentesis procedures at university hospitals, compare characteristics of patients within each specialty, and evaluate length of stay (LOS) and hospital costs. DESIGN, SETTING… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…Although LVP is considered safe, it requires patient hospital contact as often as weekly and is associated with poor quality of life and malnutrition, which together increase morbidity and mortality [7,8].…”
mentioning
confidence: 99%
“…Although LVP is considered safe, it requires patient hospital contact as often as weekly and is associated with poor quality of life and malnutrition, which together increase morbidity and mortality [7,8].…”
mentioning
confidence: 99%
“…30,31 Decisions on whether to perform paracentesis procedures at the bedside or to refer to IR are made frequently in US hospitals. 10 We are not certain why almost all surgical patients had paracentesis procedures performed in IR. This may be due to cultural factors such as preference of the attending surgeons, a belief that IR procedures are safer, or the fact that surgical residents did not receive training to perform paracentesis procedures.…”
Section: Discussionmentioning
confidence: 98%
“…We found that rates of IR referral for paracentesis procedures varied widely with a range of 0% to 100% and a mean (SD) IR referral rate of 32.41% (30.89%) among 204 University HealthSystem Consortium hospitals. 10 The decision to refer to IR at our institution was largely discretionary and did not reflect clinical parameters such as severity of liver disease or risk of bleeding in our models. 9 We also found that most clinical outcomes (procedure success rate, postprocedure bleeding, hospital readmission) were similar using either a bedside or an IR approach.…”
mentioning
confidence: 99%
“…Barsuk et al also found hospital costs to be lower when the procedure was performed by medicine, gastroenterology, or hepatology as compared with interventional radiology. 12 …”
Section: Discussionmentioning
confidence: 99%